2018
DOI: 10.1096/fj.201802094r
|View full text |Cite
|
Sign up to set email alerts
|

Tubular flow activates magnesium transport in the distal convoluted tubule

Abstract: Magnesium (Mg2+) is an important cofactor of many enzymes crucial for life; therefore, maintaining a Mg2+ balance in the body is essential. In the kidney, the distal convoluted tubule (DCT) determines the final urinary Mg2+ excretion. The nephron is subjected to variable urinary flow, but little is known about the influence of flow on Mg2+ transport. Primary cilia, which are mechanosensory organelles that sense changes in flow, are expressed on tubular epithelial cells. This study aimed to elucidate whether ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Studies have shown that FSS‐modulated ATP release is primary cilia‐dependent . Therefore, Ift140 −/− mDCT15 cells were used, where ciliogenesis is inhibited, to study the ATP extrusion upon FSS mechanosensation . After staining for the primary cilia‐specific protein ARL13B, no primary cilia were detected in Ift140 −/− cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that FSS‐modulated ATP release is primary cilia‐dependent . Therefore, Ift140 −/− mDCT15 cells were used, where ciliogenesis is inhibited, to study the ATP extrusion upon FSS mechanosensation . After staining for the primary cilia‐specific protein ARL13B, no primary cilia were detected in Ift140 −/− cells.…”
Section: Resultsmentioning
confidence: 99%
“…Both Pkd1 −/− clones used in this study were generated independently by either use of the PX458 or PX333‐GFP plasmid. The Ift140 −/− mDCT15 cell line was previously generated and validated by sanger sequencing and immunocytochemistry …”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, it was shown that several segment-specific transporters are altered due to flow, such as calcium transporters in DCT and CD 50 or magnesium transporters in DCT. 44 Transcriptomic data from tubular cell types not included in this study, e.g. the loop of Henle, and the DCT, will help to complement our understanding of flow-induced effects on cells in renal tubules in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Verschuren and colleagues used an in vitro microfluidic system to determine the effects of fluid shear stress (FSS) on Mg 21 uptake by mDCT15 cells. 67 Mg 21 uptake was stimulated, but the pathways or regulatory mechanisms are unclear. CRISPR/Cas9 disruption of intraflagellar transport 140 homolog (IFT140), which is required for primary cilium function, affected static uptake but had no effect on FSS-induced uptake.…”
Section: Distal Convoluted Tubulementioning
confidence: 99%
“…Changes in fluid flow rate cause shear stress that is detected by primary cilia or mechanosensing proteins located at the apical membrane of the renal epithelia. Verschuren and colleagues used an in vitro microfluidic system to determine the effects of fluid shear stress (FSS) on Mg 2+ uptake by mDCT15 cells 67 . Mg 2+ uptake was stimulated, but the pathways or regulatory mechanisms are unclear.…”
Section: Distal Convoluted Tubulementioning
confidence: 99%